Restrukturisasi Produk Pembiayaan Musharakah Mutanaqishah Di Bank Syariah Indonesia Dalam Etika Manajemen Koperasi Berbasis Syariah - Moh Agus Sifa'; Shelvyna Rikantasari (Journal of Islamic Banking, 2024)
This study aims to examine the implementation of the restructuring of the musharakah mutana>qishah financing product at Bank Syariah Indonesia (BSI) Bojonegoro Branch from the perspective of Islamic economic law and to assess its compliance with Islamic principles in cooperative management. The method used is qualitative with a field study approach through interviews with internal BSI parties and financing customers. The results of the study indicate that the implementation of the musharakah mutanaqishah contract at BSI Bojonegoro Branch experienced a contract engineering (hilah), where the object of the transaction is an asset that was previously fully owned by the customer. This practice is not entirely in accordance with the original characteristics of the musharakah contract, and is more like a 'inah sale and purchase scheme according to the perspective of muamalah fiqh. In the context of Islamic economic law, the transaction can be considered valid if it meets the pillars and conditions of sale and purchase, as explained in the view of the Syafi'iyah school. This study recommends BSI to review the implementation of contracts to maintain sharia integrity in financing products and encourage innovation that is oriented towards the benefit and justice for all parties.